2018
DOI: 10.1108/etpc-04-2017-0039
|View full text |Cite
|
Sign up to set email alerts
|

Tensions in learning to teach English

Abstract: Purpose The purpose of this paper is to report findings from a study of preservice teacher (PST) beliefs about teaching English language arts (ELA). Design/methodology/approach A survey was administered to 56 preservice secondary ELA teachers at three universities to measure their beliefs about curriculum, authority and competition in schools. This study explores the beliefs of 17 of these PSTs who participated in an additional interview following up on six of the survey responses. Findings Although the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…For example, teachers who asserted beliefs about the importance of student-centered curriculum and pushed against traditional grammar instruction in their student teaching reverted back to traditional worksheets when pressured by schools (Smagorinsky et al, 2007). Similarly, Dunn et al (2018) found PTs experienced tensions between socially just teaching approaches that gave more agency to students and the external constraints they imagined facing in schools, such as other teachers’ perceptions of “progressive methods” (p. 51) and pressure to teach canonical literature. Other articles reported that even when there was ideological alignment between the preparation program and classroom contexts, the methods PTs drew on most were from their own schooling histories or present contexts.…”
Section: Resultsmentioning
confidence: 99%
“…For example, teachers who asserted beliefs about the importance of student-centered curriculum and pushed against traditional grammar instruction in their student teaching reverted back to traditional worksheets when pressured by schools (Smagorinsky et al, 2007). Similarly, Dunn et al (2018) found PTs experienced tensions between socially just teaching approaches that gave more agency to students and the external constraints they imagined facing in schools, such as other teachers’ perceptions of “progressive methods” (p. 51) and pressure to teach canonical literature. Other articles reported that even when there was ideological alignment between the preparation program and classroom contexts, the methods PTs drew on most were from their own schooling histories or present contexts.…”
Section: Resultsmentioning
confidence: 99%
“…The structural and theoretical underpinnings of this study rely on an assumption that university-based ELA teacher education programs have the potential to better prepare developing educators. This potential exists because: teacher education programs have the proven capacity to profoundly shape and expand developing teacher beliefs (Dunn et al , 2018); and current constructions of these programs are not producing a sufficient quantity of effective teachers who sustain within the profession over time (Eggen and Kauchak, 2008; Glazerman et al , 2006; Palaich and Burnes, 1983; Xu et al , 2011). …”
Section: Theoretical Perspectives and Review Of Literaturementioning
confidence: 99%
“…teacher education programs have the proven capacity to profoundly shape and expand developing teacher beliefs (Dunn et al , 2018); and…”
Section: Theoretical Perspectives and Review Of Literaturementioning
confidence: 99%